DETERMINATION OF HLB VALUES OF SOME NONIONIC SURFACTANTS AND THEIR MIXTURES - KOTHENCZ, Réka; NAGY, Roland; BARTHA, László (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Advanced analytical and impact assessment methods are needed for the development of modern surfactants, so the composition, the effect and other properties of surfactants are examined by analytical tools which may be suitable for the quality testing of the raw materials, the intermediates and the final products. The HLB values of non-ionic surfactants and their mixtures were determined by three different methods: theoretical HLB based on the chemical structure and the given HLB of surfactants, the Greenwald method and an improved, titrimetric method. Our aim was to investigate if the new method to determine the water number and HLB value is suitable for this type of commercial surfactants and their mixtures. The particle size and the turbidity of micelles formed in surfactant solutions were also measured and evaluated.